L’artrodesi circonferenziale selettiva mini-invasiva nel trattamento della patologia discale degenerativa lombare - Piazzolla, A.; Bizzoca, D.; Montemurro, V.; Parato, C.; La Malfa, M.; Moretti, B. (Lo Scalpello - Journal, 2019)
MINIMALLY INVASIVE CIRCUMFERENTIAL FUSION IN LUMBAR DEGENERATIVE DISC DISEASE Degenerative lumbar spine disease is one of the leading causes of disability worldwide. Lumbar interbody fusion (LIF) is a valid approach in the treatment of several segmental spine pathologies, including degenerative disc disease. LIF may be performed through open and minimally invasive procedures. This review aims to assess the state of the art in the field of minimally invasive spine surgery in the treatment of degenerative disc disease.